Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702482
|View full text |Cite
|
Sign up to set email alerts
|

Snot, Sweat, Pain, Mud, and Snow

Abstract: We have conducted interviews with ten elite and recreational athletes to understand their experiences and engagement with endurance sport and personal and wearable sports technology. The athletes emphasized the experiential aspects of doing sports and the notion of feeling was repeatedly used to talk about their activities. Technology played both an instrumental role in measuring performance and feeding bio-data back to them, and an experiential role in supporting and enhancing the sport experience. To guide f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…Some early adopters of trackers, for example those active in the Quantified Self community can be considered extreme users, and have been found to be motivated by different reasons, including simply the desire of finding new life experiences [11]. Even elite athletes using trackers for instrumental purposes (such as improving an athletic skill), report an experiential side to the practice of tracking: it supports and enriches their sporting practice [82]. Moreover, in their stage-based model of personal informatics systems, Li and colleagues [44] showed that some people start collecting data merely because they could, and their goals and information needs become refined once they engage with collected data and understand its limitations.…”
Section: Engagements With Data: Through the Lens Of Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Some early adopters of trackers, for example those active in the Quantified Self community can be considered extreme users, and have been found to be motivated by different reasons, including simply the desire of finding new life experiences [11]. Even elite athletes using trackers for instrumental purposes (such as improving an athletic skill), report an experiential side to the practice of tracking: it supports and enriches their sporting practice [82]. Moreover, in their stage-based model of personal informatics systems, Li and colleagues [44] showed that some people start collecting data merely because they could, and their goals and information needs become refined once they engage with collected data and understand its limitations.…”
Section: Engagements With Data: Through the Lens Of Practicementioning
confidence: 99%
“…Conversely, data is not merely representational-representing some objective state "out there"-it intervenes and changes the very activities it represents. This happens in elite sports [82] and everyday usage [58,82]. Like others in the HCI community [51], we are concerned with how biodata is woven into everyday life, which interpretations are afforded by bio-sensing technologies, and how these relate to everyday practices of the users.…”
Section: Engagements With Data: Through the Lens Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Tholander and Nylander [64] pointed out the need to inform sports interactive technologies research via understanding people's first-hand experience of sports practices and technology use. Kjeldskov and Skov [35] also found that the community extensively used usability evaluation, which led to better interfaces for people to use "a mobile device in a mobile context".…”
Section: Smartphone Fitness Appsmentioning
confidence: 99%
“…Sports tracking [1], for example, has been suggested for climbing [4,5,6] and backcountry skiing [3]. The relation of performance and experience of sports watch usage has been studied in runners [9] indicating that wearable technology can improve both performance and the experience.…”
Section: Motivationmentioning
confidence: 99%